Parallel image processing system on a cluster of personal computers - J. Barbosa (2000)
The most demanding image processing applications require real time processing often using special purpose hardware. The work herein presented refers to the application of cluster computing for off line image processing, where the end user benefits from the operation of otherwise idle processors in the local LAN. The virtual parallel computer is composed by off-the-shelf personal computers connected by a low cost network, such as a 1o Mbits Ethernet, The aim is to minimise the processing time of a high level image processing package. The system developed to manage the parallel execution is described and some results obtained for the parallelisation of high level image processing algorithms are discussed namely for active contour and modal analysis methods which require the computation of the eigenvectors of a symmetric matrix.